2007
DOI: 10.1080/08923970701675085
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antitumor Immunity after Propofol Treatment in Mice

Abstract: Propofol and midazolam are the most widely used sedatives in the intensive care setting after surgery. We studied whether these sedatives had any antitumor immunity effects in mice. Mice were given intraperitoneal injections of propofol or midazolam and subcutaneous inoculation of tumor cells (EL4). Then, spleen cells were collected and the in vitro activity of cytotoxic T lymphocytes (CTL) was measured using flow cytometry. The in vitro activity of CTL against EL4 was significantly greater after propofol inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
89
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 25 publications
1
89
0
1
Order By: Relevance
“…Isoflurane, but not propofol, has been found to increase hypoxiainducible factor-1a and its downstream effectors to promote renal cell carcinoma survival [35] and, in contrast, propofol has been found to inhibit hypoxia-inducible factors in prostate cancer [38]. This is in keeping with total intravenous anaesthesia's predominantly anticancer effects from the literature, and in preclinical data, propofol inhibits invasion of cancer cells [39], is anti-metastatic [40], inhibits the proliferation and migration of oesophageal cancer [41] and induces apoptosis in non-small cell lung cancer, colon cancer and ovarian cancer cells [42].…”
Section: A Peri-operative 'Perfect Storm'supporting
confidence: 69%
“…Isoflurane, but not propofol, has been found to increase hypoxiainducible factor-1a and its downstream effectors to promote renal cell carcinoma survival [35] and, in contrast, propofol has been found to inhibit hypoxia-inducible factors in prostate cancer [38]. This is in keeping with total intravenous anaesthesia's predominantly anticancer effects from the literature, and in preclinical data, propofol inhibits invasion of cancer cells [39], is anti-metastatic [40], inhibits the proliferation and migration of oesophageal cancer [41] and induces apoptosis in non-small cell lung cancer, colon cancer and ovarian cancer cells [42].…”
Section: A Peri-operative 'Perfect Storm'supporting
confidence: 69%
“…It has been reported that propofol anaesthesia attenuates surgery-induced immune suppression [16][17][18][19]. However, little information is available about its effects on CD28 and IL-12, or if its effects differ from those of volatile agents such as isoflurane.…”
mentioning
confidence: 99%
“…Miao et al (30) has also shown that propofol is able to significantly decrease the invasive activity of human colon carcinoma cells. In animal studies (31,32), propofol exerted antitumor activities by modulating immune reaction. However, it is unclear whether propofol exhibits inhibitory effects on tumor metastasis and proliferation.…”
Section: Discussionmentioning
confidence: 99%